Sustainable and responsible finance: A concern for strong Workers' Voice - Institute for Codetermination; Corporate Governance (I.M.U.) of the Hans-Böckler-Stiftung (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2019)
Unicredit's Global Framework Agreement about "Responsible Sales in Finance" is an excellent example of how employees, their trade unions and management are able to conclude a common understanding of the company's overall business orientation. Political action for more workers' voice on European level is needed.
Keywords: 330; co-determination; finance; UN; EU; sustainability; global framework agreement